Comparing feed use efficiency and enteric gas production of Holstein and Jersey cows in a kikuyu pasture-based system using mathematical models - Bangani, Noluvuyo Muriel (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.